Current management of button battery injuries. Issue 3 (15th April 2021) - Sethia, Rishabh; Gibbs, Hannah; Jacobs, Ian N.; Reilly, James S.; Rhoades, Keith; Jatana, Kris R.
Abstract: Button batteries (BB) are found in common household items and can lead to significant morbidity and mortality in the pediatric population when ingested. BBs are made of various chemistries and have a unique size and shape that yield significant injury when lodged in the pediatric esophagus. BBs create a local tissue pH environment of 10 to 13 and can induce liquefactive necrosis at the negative pole. This initial injury can progress with further tissue breakdown even after removal. Unfortunately, patients may present with vague symptoms similar to viral illnesses and there is not always a known history of ingestion. Plain film X‐ray can be diagnostic. Exposure can lead to caustic injury within 2 hours. Thus, timely endoscopic removal is the mainstay of treatment. Novel mitigation and neutralization strategies have been implemented into treatment guidelines. These include the preremoval ingestion of honey or sucralfate and intraoperative irrigation with acetic acid. Depending on the severity of injury following removal, careful consideration should be given for potential delayed complications including fistulization into major vessels which often leads to death. The National Button Battery Taskforce and several industry members have implemented prevention strategies such as educational safety outreach campaigns, child‐resistant packaging changes, and warning labels. Governmental regulation and industry changes are key to limit not only the amount of BB ingestions, but also the devastating consequences that can result. Anonymous reporting of BB injuries through the Global Injury Research Collaborative has been made convenient and centralized through the advent of a user‐friendly smartphone iOS/App Store and Android/GooglePlay application called the "GIRC App"; all specialists who manage foreign body cases should contribute their cases to help prevent future injuries. BB ingestion must be recognized and treated promptly using a multidisciplinary approach to optimize outcomes for these patients. Ultimately, a safer BB technology is critically needed to reduce or eliminate the severe and life‐threatening injuries in children. Level of Evidence: 5